Cannabinoid Receptor 1 Participates in Liver Inflammation by Promoting M1 Macrophage Polarization via RhoA/NF-κB p65 and ERK1/2 Pathways, Respectively, in Mouse Liver Fibrogenesis - Tian, Lei; Li, Weiyang; Yang, Le; Chang, Na; Fan, Xiaoting; Ji, Xiaofang; Xie, Jieshi; Yang, Lin; Li, Liying (Frontiers in Immunology, 2017)
Macrophage M1/M2 polarization mediates tissue damage and inflammatory responses. Cannabinoid receptor (CB) 1 participated in liver fibrogenesis by affecting bone marrow (BM)-derived monocytes/macrophages (BMMs) activation. However, the knowledge of whether CB1 is involved in the polarization of BMMs remains limited. Here, we found M1 gene signatures (including CD86, MIP-1β, TNF, IL-6 and iNOS) and the amount of M1 macrophages (CD86+ cells, gated by F4/80) were significantly elevated in carbon tetrachloride (CCl4) -induced mouse injured livers, while that of M2 type macrophages had little change by RT-qPCR and Fluorescence-activated cell sorting (FACS). Our preceding study confirmed CB1 was involved in CCl4-induced liver fibrogenesis. Our results noted CB1expression showed positive correlation with CD86. Blockade of CB1 by its antagonist or siRNA in vivo down-regulated the mRNA and protein levels of M1 markers using RT-qPCR, Western blot and Cytometric Beads Array (CBA) assays, and reduced the proportion of M1 macrophages. Moreover, chimera mouse models, which received BM transplants from EGFP-transgenic mice or clodronate liposome injection mouse models, in which Kupffer cells were depleted, were performed to clarify the role of CB1 on the polarization of Kupffer cells and BMMs. We found that CB1 was especially involved in BMM polarization towards M1 phenotype but have no effect on that of Kupffer cells. The reason might due to the lower CB1 expression in Kupffer cells than that of BMMs. In vitro, we discovered CB1 was involved in the polarization of BMMs towards M1. Furthermore, CB1-induced M1 polarization was apparently impaired by PTX (G()i/o protein inhibitor), Y27632 (ROCK inhibitor) and PD98059 (ERK inhibitor), while SB203580 (p38 inhibitor) and compound C (AMPK inhibitor) had no such effect. ACEA (CB1 agonist) activated G()i/o coupled CB1, then enlarged GTP-bound Rho and phosphor-ERK1/2, independently. NF-κB p65 nuclear translocation is also a maker of M1 phenotype macrophages. We found that CB1 switched on NF-κB p65 nuclear translocation only depending on G()i/o/RhoA signaling pathway. Conclusions: CB1 plays a crucial role in regulating M1 polarization of BMMs in liver injury, depending on two independent signaling pathways: G()i/o/RhoA /NF-κB p65 and G()i/o/ERK1/2 pathways.